Factors associated with sustainability of agripreneurship interest among graduate youth in Southwestern Nigeria - Alabi, Dorcas Lola; Aribifo, Damilola Leah; Famakinwa, Michael (Applied Studies in Agribusiness and Commerce, 2021)
The paper examined factors associated with sustainability of agripreneurship interest of graduate youth in Southwestern Nigeria. It specifically described the socio-economic characteristics of the respondents; identified their agripreneurship activities of interest and identified factors associated with their interest. A multi-stage sampling procedure was used to select 185 respondents from the selected the Local Government Areas in Southwestern States, quantitative and qualitative data were collected using semi structured questionnaire and Focus Group Discussion (FGD) respectively. Data were analyzed using descriptive statistical tool such as frequency counts, percentages, means and standard deviation while factor analysis was used to isolate crucial factors associated with sustainability of agripreneurship interest of serving graduate youth in the study areas. Results showed that respondents had a mean age of 26.18 ± 2.74 years and majority (75.7%) were not graduates of agriculture. The agricultural enterprises of interest to the respondents were poultry farming (67.6%)’ fish farming (56.5%) and snail farming (50.9%). Crucial factors found to influence sustainability of graduate youth’s interest in agripreneurship were motivational, parental influence, community asset and institutional factors among other. The study concluded that these identified factors were germane to the sustainability of graduate youth’s interest in agripreneurship in Southwestern Nigeria.